2008
DOI: 10.1098/rspb.2008.1374
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive skew in female common marmosets: what can proximate mechanisms tell us about ultimate causes?

Abstract: Common marmosets are cooperatively breeding monkeys that exhibit high reproductive skew: most subordinate females fail to reproduce, while others attempt to breed but produce very few surviving infants. An extensive dataset on the mechanisms limiting reproduction in laboratory-housed and freeliving subordinate females provides unique insights into the causes of reproductive skew. Non-breeding adult females undergo suppression of ovulation and inhibition of sexual behaviour; however, they receive little or no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 98 publications
(220 reference statements)
3
73
0
Order By: Relevance
“…First, subordinate females commonly exhibit down-regulated reproductive physiologies when in the presence of the dominant female (e.g. Clarke et al 2001;Saltzman et al 2009). This may be due either to the subordinate exercising physiological restraint given a threat of interference by the dominant (Young et al 2008;Saltzman et al 2009) or to the dominant forcibly downregulating the subordinates' fertility by subjecting them to chronic stress (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First, subordinate females commonly exhibit down-regulated reproductive physiologies when in the presence of the dominant female (e.g. Clarke et al 2001;Saltzman et al 2009). This may be due either to the subordinate exercising physiological restraint given a threat of interference by the dominant (Young et al 2008;Saltzman et al 2009) or to the dominant forcibly downregulating the subordinates' fertility by subjecting them to chronic stress (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the finding also suggests that reproductive coercion may extend well beyond the systems in which infanticide is common. Hidden threats of policing can deter subordinates from reproducing in the first place (44)(45)(46), or select for counterstrategies [such as synchronous birth (26,37), egg-laying (47), or egg-mimicry (48)] to render threats noncredible (i.e., unprofitable for a threatening individual to carry out, in the event that a transgression occurs). In both cases, threats of infanticide influence reproductive behavior even though no offspring are killed.…”
Section: Resultsmentioning
confidence: 99%
“…for reproductive toxicology and or fertility suppression). We wanted to investigate whether the endocrine regulation of testicular function in the marmoset ) and the strong social component regulating reproduction and natural fertility in this species (Abbott et al 1988, Saltzman et al 2009 allow studies that enable translation of findings to the human situation.…”
Section: Discussionmentioning
confidence: 99%
“…This is a unique feature among available NHP models (Saltzman et al 2009). In males, there are no data available on whether spermatogenesis is suppressed to some extent; however, it has been demonstrated that offspring are almost exclusively sired by the dominant male (Nievergelt et al 2000) and supported by the lack of sexual dimorphism in marmosets, a monogamous mating system was suggested (Abbott & Hearn 1978).…”
Section: Nete and Tu Contraception Fails In Marmosetsmentioning
confidence: 99%